Two new free living mite species of Eustigmaeus (Actinedida: Raphignathoidea: Stigmaeidae) from Poland, with new data of some other rare species of the genus - Kaîmierski, Andrzej; Dończyk, Justyna (Zootaxa, 2003)
Two new species of the genus Eustigmaeus Berlese, 1910 (E. formosus sp. n. and E. brevivestitus sp. n.) from North Poland are described and figured. The second world record of E. microsegnis (Chaudhri, 1965), as well as new data of E. myrtea (Chaudhri, 1965) and E. pinnatus (Kuznetzov, 1977) are added.